Consumer Behavior and Attributes that Indicate the Preferences of Retail Formats in the Sector Personal Care, Perfume And Cosmetics - Tamashiro, Helenita R. da Silva (2011)
Facing increased competition, which intensified the process of economic liberalization in 1990, the Brazilian retail sector is undergoing a transformation process. This process is conducted on two levels. On one side is the growing concentration of income from a small proportion of the population in the country and the other is the low purchasing power of thousands of consumers, which in turn represents a significant buying potential. This scenario has been putting in check the strategies adopted by a majority of the retail section. The objective of the work was to identify which is the retail format preferred by the consumers of personal hygiene products, perfumery and cosmetics. The research was conducted under the hypothesis that the neighborhood supermarkets constitute the format of favorite retail for those consumers. A survey was conducted,, starting from a sampling no-probabilistic intentional, with 400 respondents of the So Paulo state. The results obtained through structured questionnaires show that the favorable formats are, respectively, the pharmacies and drugstores, the specialized stores and direct sale (catalog), refuting the hypothesis proposed in the study.